Big data a problem reprezentacji poznawczej - Iwasiński, Łukasz (Człowiek i Społeczeństwo, 2022)
In this article, the author reflects on Big Data analytics in the context of the problem of cognitive representation. There are many voices declaring that the era of Big Data has brought a radical breakthrough in human cognitive abilities. Some – especially in the world of business and marketing, and to a lesser extent in the field of science – argue that for the first time we can reach a clean, objective picture of reality and keep track of its changes. The article is a critical commentary to this thesis. In Big Bata analytics, cognitive activities are assessed not from the point of view of their compliance with reality, but the possibility of achieving set goals. Big Data mining can be, and often is, an important tool for reality control and forecasting – which does not mean it can discover objective truth and create accurate representations of reality.